2019
DOI: 10.1016/j.proci.2018.06.075
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and extinction of premixed edge-flames

Abstract: The propagation rates (Uedge) of edge-flames in premixed hydrocarbon-oxygen-inert mixtures were measured as a function of global strain rate (σ), mixture strength, and (by changing fuel and inert type) Lewis number (Le). Using a counterflow slot-jet burner with electrical heaters at both ends to anchor the flame edges, both advancing (positive Uedge) and retreating (negative Uedge) edge-flames were characterized. Results are presented for both twin (premixed gas against premixed gas) and single (premixed gas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The following observations are made:  The majority of the samples feature a stabilization velocity larger than 3SL  0.43 m/s (for  = 1 at 7 bar), which was shown to provide an upper bound of the speed of an edge-flame [11,18,[46][47][48]. In previous studies, edge-flame speeds larger than 3SL were only reported for Lewis numbers larger than unity [48] or twin premixed edge-flames [49], which is not the case here.…”
Section: Flame Base Structurementioning
confidence: 86%
“…The following observations are made:  The majority of the samples feature a stabilization velocity larger than 3SL  0.43 m/s (for  = 1 at 7 bar), which was shown to provide an upper bound of the speed of an edge-flame [11,18,[46][47][48]. In previous studies, edge-flame speeds larger than 3SL were only reported for Lewis numbers larger than unity [48] or twin premixed edge-flames [49], which is not the case here.…”
Section: Flame Base Structurementioning
confidence: 86%